Food environment components influencing consumption trends of neglected and underutilized species in northern Benin - Bissola Malikath Verena Bankole; Waliou Amoussa Hounkpatin; Sam Bodjrenou; Julia Bodecker; Lynn Julen; Flora Josiane Chadare; Celine Termote (PLoS ONE, 2025)
Malnutrition is a global problem driven by food systems that impact climate and biodiversity. Neglected and underutilized species (NUS) could improve diets, but what drives their choices and consumption, particularly in low and middle-income countries, is poorly documented. This study investigated the influences of the personal food environment on the consumption of NUS in three communities in the department of Atacora in northern Benin. Following a purposive sampling strategy, 24 semi-structured interviews were conducted with locals and 18 with professional experts. 12 group discussions with villagers from six villages in the three communes complemented and deepened the information gathered, focusing on both barriers and factors for enhancing consumption. The data collected was translated and transcribed into French and analyzed using qualitative content analysis with Atlas.ti software. Among the investigated plant parts, an upward trend was found for Moringa oleifera leaves and Vigna radiata seeds, a downward trend for Adansonia digitata pulps, and a varied trend for Ocimum gratissimum leaves and Adansonia digitata kernels and leaves. Drivers for changes in consumption were found in all four dimensions of the food environment. Among the plant parts with the main increasing trend in consumption, various aspects of desirability, above all increased food and nutrition knowledge and skills, led to a positive consumption trend. The downward trend has most often been attributed to declining accessibility, but several aspects have also made these plant parts less affordable and less desirable (taboos for example). The strong variation in dimensions’ influence on plant parts with variable trends reflects their non-unanimous changes. Research and policies should address the factors influencing the consumption of these foods. Making neglected species more accessible, affordable, and desirable can enhance food security and environmental sustainability.